Deteksi Alih Fungsi Lahan Padi Sawah Menggunakan Sentinel-2 dan Google Earth Engine di Kota Serang, Provinsi Banten - Tian Mulyaqin; Kardiyono Kardiyono; Ismatul Hidayah; Fadhlullah Ramadhani; Muchamad Yusron (Jurnal Ilmu Pertanian Indonesia, 2022)
Land is one of the main factors in rice production. However, the transfer of agricultural land functions to other sectors continues and becomes a challenge in the food supply in Indonesia. Serang City is one of the rice-producing areas in Banten Province. This study aims to analyze changes in the transfer of rice field functions to other sectors by mapping rice field cover using Sentinel-2 satellite imagery in 2021 compared to 2019 with the Random Forest method by using Google Earth Engine (GEE) applications and cloud computing support. The study results showed that the cover of rice fields in Serang City in 2021 decreased by 602.87 ha (-7.20%) compared to 2019 from the total land cover. Land cover in other vegetation was also reduced by 242 ha (-2.45%), while urban land cover in 2021 increased by 781.82 ha (10.89%). This study shows that there has been a change in land transfer in Serang City due to urban expansion in 3 years, as well as that the use of GEE can streamline monitoring of changes in land transfer and land use cover. Keywords: rice field, Google Earth Engine, Sentinel-2